TEACHING ENGLISH VOCABULARY BASED REALIA KITS AT SDN 35 TAJUNCU - Jusmaniar N; Sitti Nurjanna; Sulviana Sulviana; Abdullah Abdullah (ALGAZALI INTERNATIONAL JOURNAL EDUCATIONAL RESEARCH, 2020)
Abstract: Teaching English Vocabulary based Realia Kits at SDN 35 Tajuncu.This study aims to find out teachers’ perception on Realia Kits used, students’ interest, and types of Realia Kits used in teaching English. This is a Descriptive Qualitative Study, located in SD Negeri 35 Tajuncu. Informants as the object of research are Teachers of SD Negeri 35 Tajuncu who teach English. Researchers used interview, observation, and documentation as instruments in collecting data.Based on the results of data analysis, teachers responded the kits positively. In line with the observation which were used to measure students’ interest, it was found that students of SD Negeri 35 Tajuncu had high interest in Realia as teaching media. Moreover, From three types of Realia, ‘Unmodified Real Things’ was the most applicative type.Keywords: English, Realia Kits, Perception, Interest.